IMPLEMENTASI PERDA NOMOR 2 TAHUN 2012 TENTANG RTRW KABUPATEN LOMBOK TIMUR TAHUN 2012-2032 DALAM PERSPEKTIF PENGENDALIAN PEMANFAATAN RUANG - Deden Barliahadi; Agus Suryono; Choirul saleh (Universitas Tribhuwana Tunggadewi, 2015)
Spatial Plan is accompanied by Spatial Plan Bylaw East Lombok No. 2 of 2012 as a guideline for use and control of space in East Lombok district . To oversee the implementation of the regulation , established the Regional Spatial Planning Coordinating Board of East Lombok (BKPRD) which has the task and the main function is to supervise and control the use of space . However, in practice since the publication of the Spatial regulation , there are still many land use changes and uncontrollable due to the need for space for the community , public and private , as well as granting permissions that are not in accordance with the rules contained in the spatial plan . The method used is qualitative methods of data collection techniques of interview , observation and document study . The findings of the field that BKPRD East Lombok as the implementor of the Spatial Regulation of East Lombok not have good management in the execution of its duties and functions